Online Engineering and Society 4.0 Proceedings of the 18th International Conference on Remote Engineering and Virtual Instrumentation - Auer, Michael E.; Bhimavaram, Kalyan Ram; Yue, Xiao-Guang (Lecture Notes in Networks and Systems, 2022)
XVIII, 572 p. 335 illus., 308 illus. in color.